A Randomized Controlled Trial to Assess the Effectiveness of Nurse -Led Structured Telephonic Heart Failure Management Programme on Selected Health Related Outcome Variables Among Patients of Heart Failure At 3 Months. - Dr.L.Gopichandran, Prof. Sandeep Seth, Dr. Deepak Sharma, Dr. Manoj Kumar, Ms. Dainy Thomas, Mr. Subeen P.D., Ms. Divya Sojan, Ms. Ankita Sharma (Drugs and Cell Therapies in Hematology, 2021)
Nurses are the pillars of healthcare system, they are required to provide care to patients suffering with different kinds of illness either acute, subacute or chronic. Patients suffering with heart failure are chronically ill, requiring constant monitoring of vital signs, counselling based upon the changing pattern of vital signs. Telemonitoring has extended a help in management of these patients with constant exchange of healthcare data and information. Objective is to assess the efficacy of Nurse -Lead Structured Telephonic Heart Failure Management Programme on selected health related outcome variables as Quality of life, NYHA classification, Dug compliance, BNP levels among patients of heart failure at 3 months. Methodology is 50 participants in each group were allocated randomly. Pre (baseline) and post (3 months) intervention measurements include assessment of Quality of life, NYHA classification, Dug compliance, BNP levels . Intervention includes health teaching, Dhadkan App & structured telephonic follow up conducted by investigator to HF patients who visit HF clinic. Results are as groups were comparable in terms of demographic and clinical profile as baseline. In post-test, there was statistically significant improvement in Quality of life(p-0.019), drug compliance (p-<0.001), while no improvement was seen in BNP value. Conclusion- Nurse -Led Structured Telephonic Heart Failure Management Programme was effective in improving in quality of life, drug compliance among HF patients.